PKK EMPOWERMENT IN PADALUYU VILLAGE IN PSYCHOSOCIAL AND SPIRITUAL ASSISTANCE FOR EARTHQUAKE SURVIVORS, CUGENANG DISTRICT, CIANJUR REGENCY - Sadiyah, Maemunah; Rahman, Imas Kania; Lisnawati, Santi; Wahdani, Ira; Aulia Ramadhan, Nabil; Shabirrania Darmawan, Naura (LPPM Univ. Ibn Khaldun Bogor, 2023)
Disasters have long-term psychological impacts, both visible ones such as depression and psychosomatic as well as invisible ones such as family conflicts to divorce. On November 22, 2022, an earthquake occurred in Cianjur Regency, the worst condition was in Cugenang District. The disaster that occurred affected the stability of residents' lives due to the loss of family members, residences, closed access roads, loss of business land as well as other properties. Apart from that, the survivors witnessed their houses collapse without remains, and the people closest to them died or were injured, the frightening earthquake incidents have affected their mental health so that they become afraid, withdraw from their environment, have difficulty managing their emotions, are not calm, and worry all the time. There need to be psychological assistance services in the form of assistance for survivors of severe, moderate, and mild trauma. Intensive assistance can only be carried out by trained personnel who are ready to live close to survivors. The Padaluyu PKK mobilizing group has the potential to be trained (TOT). 35 representatives from each RT were selected to be trained in healing and art therapy materials. Then the 10 best participants were selected accompanied by 10 BKPI students to implement their abilities to assist survivors in RW 07 RT 03 Kampung Barujamas Padaluyu in three categories of survivors children, youth, and adults. Testimonials from 10 PKK activists and Barujamas residents stated that the mentoring program was very useful.